TurningPoint: Narrative-Driven Presentation Planning - Pschetz, Larissa; Yatani, Koji; Edge, Darren (CHI 2014 Conference on Human Factors in Information Systems, 2014)
Once upon a time, people told stories unencumbered by slides. What modern presentations gain through visual slide support, however, is often at the expense of storytelling. We present TurningPoint, a probe to investigate the potential use of narrative-driven talk planning in slideware. Our study of TurningPoint reveals a delicate balance between narrative templates focusing author attention in ways that save time, and fixating attention in ways that limit experimentation.
Honorable Mention Award